e-UKBM BERBASIS PROBLEM BASED LEARNING PADA MATERI SISTEM PERSAMAAN LINEAR TIGA VARIABEL - Fenny Fridiana Lifira; Latifah Mustofa Lestyanto (FMIPA UNIVERSITAS NEGERI MALANG, 2020)
Errors in solving mathematical problems occur mainly at the stage of transforming the problem. The use of e-UKBM which has not yet led students to discover the knowledge acquired is one of the causes. Hence, research and development of e-UKBM based on Problem Based Learning on the material of the Three Variable Linear Equation System that can train students' problem-solving skills can be conducted,. This study modifies the 4D model which includes the stages of defining, designing, developing and disseminate. However, the disseminate stage was not carried out due to limited research time. The e-UKBM product is tested for its validity, practicality, and effectiveness. Based on the results of the study, e-UKBM was declared valid, practical, and effective.Keywords: e-UKBM, Problem Based Learning, Three Variable Linear Equation System